The Application of Case-Based Reasoning to Early Software Project Cost Estimation and Risk Assessment - Delany, Sarah Jane; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2000)
In this paper we assess the applicability of case-based reasoning to the difficult problem of early software project cost estimation. We conclude that a comprehensive case representation is not available early in the project and suggest instead that the objective should be risk assessment rather than cost estimation. In reaching this conclusion the existing techniques for cost estimation are discussed and evaluated. A case representation capturing the available predictive features for early estimation is identified and presented. The lack of features to predict size early in the development life cycle indicates a limitation of the conventional CBR model ? and indeed any knowledge-based approach. If a complete problem representation is not available an automated reasoning mechanism will not be able to produce good cost estimates. The alternative we propose is to focus on a measure called the productivity coefficient rather than the expected effort. The productivity coefficient gives a measure of the potential risk revealed by the characteristics of a project compared with previous project experiences. The utility of this approach is described in a sample scenario.
Keywords: Computer Science